2015
DOI: 10.1242/jeb.120907
|View full text |Cite
|
Sign up to set email alerts
|

Embryo oxygenation in pipefish brood pouches: novel insights

Abstract: The pipefish brood pouch presents a unique mode of parental care that enables males to protect, osmoregulate, nourish and oxygenate the developing young. Using a very fine O 2 probe, we assessed the extent to which males of the broad-nosed pipefish (Syngnathus typhle) oxygenate the developing embryos and are able to maintain pouch fluid O 2 levels when brooding in normoxia (100% O 2 saturation) and hypoxia (40% O 2 saturation) for 24 days. In both treatments, pouch fluid O 2 saturation levels were lower compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 57 publications
(68 reference statements)
3
28
0
Order By: Relevance
“…These results are in line with recent measurements that showed that, in S. typhle, oxygen levels within the pouch were substantially lower than in the surrounding waters, both in normoxia and in hypoxia (Braga Goncalves et al. 2015a). In terms of behavior, we found that ventilation rates and proportion of time spent in the top half of the water column increased significantly in hypoxia (discussed below in relation to the brood pouch).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in line with recent measurements that showed that, in S. typhle, oxygen levels within the pouch were substantially lower than in the surrounding waters, both in normoxia and in hypoxia (Braga Goncalves et al. 2015a). In terms of behavior, we found that ventilation rates and proportion of time spent in the top half of the water column increased significantly in hypoxia (discussed below in relation to the brood pouch).…”
Section: Discussionmentioning
confidence: 99%
“…2002; Stölting and Wilson 2007; Ripley 2009; Braga Goncalves et al. 2015a,b). Given these observations, it has been proposed that parental care in fishes may have evolved, at least partially, to protect developing embryos from hypoxia (Kolm and Ahnesjö 2005), possibly as a consequence of selection of larger egg sizes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies of Syngnathidae and their reproductive biology have indicated that the physiological costs of male pregnancy become more evident in the later stage of the pregnancy (Goncalves et al. 2015; Paczolt and Jones 2015). Therefore, the lack of support for any costs of paternal care in light of investment into metabolically expensive organs should be taken with caution.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, brooding males reduce food intake (Svensson 1988; Ahnesjo 1992) while they oxygenate (Goncalves et al. 2015), provide nutrition (Sagebakken et al. 2010; Kvarnemo et al.…”
Section: Introductionmentioning
confidence: 99%